2013
DOI: 10.1103/physrevlett.110.018301
|View full text |Cite
|
Sign up to set email alerts
|

Polydispersity for Tuning the Potential of Mean Force between Polymer Grafted Nanoparticles in a Polymer Matrix

Abstract: We present an integrated theory and simulation study of polydisperse polymer grafted nanoparticles in a polymer matrix to demonstrate the effect of polydispersity in graft length on the potential of mean force between the grafted nanoparticles. In dense polymer solutions, increasing polydispersity in graft length reduces the strength of repulsion at contact and weakens the attractive well at intermediate interparticle distances, completely eliminating the latter at high polydispersity index. The reduction in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 16 publications
11
110
0
Order By: Relevance
“…22,24,26,33,37,42,50,88,90,95,109,[119][120][121][122]125,[143][144][145][146][147][148][149][150] Ganesan et al 22 have shown that the morphologies adopted by grafted NPs in a selective solvent are sensitively determined by the ratio of the NP core size to the native size of the polymeric grafts. Recent work by Jayaraman, 88,89,92 which is in good agreement with experiments, illustrates that the polydispersity of graft lengths can play a critical role in the miscibility of NPs in a polymer matrix with the same chemistry as the brush.…”
Section: Grafted Nanoparticlessupporting
confidence: 60%
See 1 more Smart Citation
“…22,24,26,33,37,42,50,88,90,95,109,[119][120][121][122]125,[143][144][145][146][147][148][149][150] Ganesan et al 22 have shown that the morphologies adopted by grafted NPs in a selective solvent are sensitively determined by the ratio of the NP core size to the native size of the polymeric grafts. Recent work by Jayaraman, 88,89,92 which is in good agreement with experiments, illustrates that the polydispersity of graft lengths can play a critical role in the miscibility of NPs in a polymer matrix with the same chemistry as the brush.…”
Section: Grafted Nanoparticlessupporting
confidence: 60%
“…(i) Phase diagrams: The theoretical/simulation works of Schweizer,46,[75][76][77][78][79] Striolo,60,[80][81][82][83] Roan,84,85 Pakula, 86,87 Jayaraman, 24,37,[88][89][90][91][92][93][94][95] de Pablo, [96][97][98][99][100][101][102] Panagiotopoulos, 50,56,[103][104][105] Grest, 34,42,71,[106][107][108][109][110][111][112][113][114] …”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has, therefore, been devoted to understand the morphological and dynamical phase diagram of such blends and the consequent role it plays in determining the physical properties of these materials [5][6][7][8][9][10][11][12][13] . On the basis of these studies, various strategies are therefore being devised to enhance the dispersibilty of various functional nanoparticles in PNCs [5][6][7][8][9][10][11][12][13][14][15] . It is believed 4,8,11,13 that a wetting nanoparticle-polymer interface is required for homogeneous nanoparticle dispersion in bulk PNCs.…”
mentioning
confidence: 99%
“…And, how does ''polydisperse grafted polymer distribution'' improve grafted particle dispersion in a matrix compared to a bidisperse grafted polymer length distribution? To address this, in a more recent study, 1 we studied effects polydispersity in graft length on the PMF between the grafted nanoparticles, varying the PDI of the grafted chains from 1 to 2.5.…”
Section: Feature Articlementioning
confidence: 99%